Respostas
respondido por:
9
Olá, Tudo bem estudante?
Bom.....Vamos Começar!
( 5x2-4x+7 ) - ( 3x2+7x-1 ) = -17
Bom.....Vamos Começar!
( 5x2-4x+7 ) - ( 3x2+7x-1 ) = -17
respondido por:
25
(5x² - 4x + 7) - (3x² + 7x - 1) =
5x² - 3x² - 4x - 7x + 7 + 1 =
2x² - 11x + 8 {resultado final}.
Regra de Sinais:
+ + = +
- - = +
+ - = -
- + = -
5x² - 3x² - 4x - 7x + 7 + 1 =
2x² - 11x + 8 {resultado final}.
Regra de Sinais:
+ + = +
- - = +
+ - = -
- + = -
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás